Knockout of interleukin-17A diminishes ventricular arrhythmia susceptibility in diabetic mice via inhibiting NF-κB-mediated electrical remodeling - Li De-sheng; Xue Gen-long; Yang Ji-ming; Li Chang-zhu; Zhang Rui-xin; Tian Tao; Li Zheng; Shen Ke-wei; Guo Yang; Liu Xue-ning; Wang Jin; Lu Yan-jie; et al. (Acta Pharmacologica Sinica, 2022)
Interleukin-17A (IL-17), a potent proinflammatory cytokine, has been shown to participate in cardiac electrical disorders. Diabetes mellitus is an independent risk factor for ventricular arrhythmia. In this study, we investigated the role of IL-17 in ventricular arrhythmia of diabetic mice. Diabetes was induced in both wild-type and IL-17 knockout mice by intraperitoneal injection of streptozotocin (STZ). High-frequency electrical stimuli were delivered into the right ventricle to induce ventricular arrhythmias. We showed that the occurrence rate of ventricular tachycardia was significantly increased in diabetic mice, which was attenuated by IL-17 knockout. We conducted optical mapping on perfused mouse hearts and found that cardiac conduction velocity (CV) was significantly decreased, and action potential duration (APD) was prolonged in diabetic mice, which were mitigated by IL-17 knockout. We performed whole-cell patch clamp recordings from isolated ventricular myocytes, and found that the densities of Ito, INa and ICa,L were reduced, the APDs at 50% and 90% repolarization were increased, and early afterdepolarization (EAD) was markedly increased in diabetic mice. These alterations were alleviated by the knockout of IL-17. Moreover, knockout of IL-17 alleviated the downregulation of Nav1.5 (the pore forming subunit of INa), Cav1.2 (the main component subunit of ICa,L) and KChIP2 (potassium voltage-gated channel interacting protein 2, the regulatory subunit of Ito) in the hearts of diabetic mice. The expression of NF-κB was significantly upregulated in the hearts of diabetic mice, which was suppressed by IL-17 knockout. In neonatal mouse ventricular myocytes, knockdown of NF-κB significantly increased the expression of Nav1.5, Cav1.2 and KChIP2. These results imply that IL-17 may represent a potential target for the development of agents against diabetes-related ventricular arrhythmias.